95 GHz ESEEM of radical pairs: a source of radical separations and relative orientations - Fursman, C; Bittl, R; Zech, S; Hore, P (2001)
W-band (95 GHz) electron spin echo envelope modulation (ESEEM) is proposed as a method for simultaneously determining the relative orientation and separation of the constituents of spin-correlated radical pairs in the solid state. The discussion focuses on the transient secondary radical pair in bacterial photosynthetic energy conversion. © 2001 Elsevier Science B.V.